Android-Based Bus Vehicle Maintenance Application Design at PT. Sumber Jaya Trans Tangerang - Syihabudin Alawi; Utomo Budiyanto (Jurnal Teknologi Informasi dan Pendidikan, 2023)
Sumber Jaya Trans is a tourism bus transportation company whose goal is to make tourism easier. Maintenance of bus vehicles is required because of their long-term use. At PT. Sumber Jaya Trans Tangerang has problems, namely vehicle maintenance in terms of data reporting which is still manual, maintenance reports are carried out on a paper form filled in by mechanics who have repaired bus vehicles and recapitulated into the ledger, managers have difficulty viewing or checking maintenance reports, because lots of paper forms and disorganized ledgers. Due to the issues at hand, the author suggests an Android-based bus vehicle maintenance app. utilizing the PIECES technique of analysis. The programming languages for Web Services and Android are PHP and the Laravel framework, respectively, and object-oriented analysis techniques are used in the system architecture together with the Unified Modeling Language (UML). Android was selected as the mobile operating system because it is well-liked in Indonesia and felt capable of replacing manual labor. In order to improve the effectiveness and efficiency of reporting vehicle maintenance data, we require an Android-based solution